TINJAUAN HUKUM TERHADAP TINDAKAN CYBERBULLYING OLEH REMAJA DAN PENCEGAHAN DALAM KONTEKS UNDANG-UNDANG ITE - Agustin Pratama Sihotang; Depi Yohana Manurung, Friska Lorentina Purba, Limra G.M. Nababan, Nasywa Yasmin Purba, Ramsul Yandi (Jurnal Komunikasi, 2023)
This paper discusses Cyberbullying by Adolescents and Prevention in the Context of the ITE Law. Cyberbullying is something that should not be envied because behavior is intended to insult, frighten, or humiliate and hurt the heart of someone who is targeted for bullying so as to trigger debate and conflict which is usually underestimated and does not think about the impact. Spreading lies about someone by insulting or posting derogatory, embarrassing photos about someone on social media so that others can also see them.The method we used this time is the research method that the author uses is a qualitative method. Through this method, the author will describe the problem discussed based on relevant data obtained and interpret the data in question as an analysis process to find relevance between variables. The author goes through the Interview method (Interview), interviews are conducted with competent or authorized parties and who are considered to know and understand the problems of researchers to provide information and information in accordance with what is needed by researchers.The result of this study is that it can be concluded that Cyberbullying is bullying that uses digital technology. Cyberbullying is something that should not be envied because behavior is intended to insult, frighten, or humiliate and hurt the heart of someone who is targeted for bullying so as to trigger debate and conflict which is usually underestimated and does not think about the impact. The impact of cyberbullying has major and bad consequences and influences on the physical and mental health of children (victims)